2021
DOI: 10.1080/10511970.2021.1881849
|View full text |Cite
|
Sign up to set email alerts
|

Supporting Computational Apprenticeship Through Educational and Software Infrastructure: A Case Study in a Mathematical Oncology Research Lab

Abstract: There is growing awareness of the need for mathematics and computing to quantitatively understand the complex dynamics and feedbacks in the life sciences. Although several institutions and research groups are conducting pioneering multidisciplinary research, communication and education across fields remain a bottleneck. The opportunity is ripe for using education research-supported mechanisms of cross-disciplinary training at the intersection of mathematics, computation, and biology. This case study uses the c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 61 publications
0
1
0
Order By: Relevance
“…By combining graduate and undergraduate students in regular lab meetings, we foster both education and research. Undergraduates learn more about active research projects (like the Studio and models developed using it); graduate students, postdocs, and staff become mentors [ 17 ] . …”
Section: Design and Developmentmentioning
confidence: 99%
“…By combining graduate and undergraduate students in regular lab meetings, we foster both education and research. Undergraduates learn more about active research projects (like the Studio and models developed using it); graduate students, postdocs, and staff become mentors [ 17 ] . …”
Section: Design and Developmentmentioning
confidence: 99%
“…It prepares a new generation of scientists proficient in both biological and computational sciences, fostering innovation in biomedical research. Additionally, it facilitates interdisciplinary collaborations, contributing to advancements in personalized medicine, drug discovery, and our comprehension of complex biological systems (262).…”
Section: Challenges and Opportunities In Bioinformatics Trainingmentioning
confidence: 99%
“…They identified that most such students seek to use computational modeling to answer domain-specific research questions that cannot be answered in wet labs. It shows that many scientists with the minimum computational background are potential users of computational modeling and simulation tools.Madamanchi et al [6] discussed the need for user-friendly tools in computational modeling training, along with the potential of using focused web applications ("microapps") for education and training. In this report, we demonstrate a suite of microapps to address the training needs of new multidisciplinary users of biological simulation software.…”
Section: Introductionmentioning
confidence: 99%